THE EFFECT OF HEALTH EDUCATION ON INCREASING BEHAVIOR FOR THE PREVENTION OF DENGUE HEMORRHAGIC FEVER IN THE COMMUNITY - Putra, Kusuma Wijaya Ridi; Riesmiyatiningdyah, Riesmiyatiningdyah; Diana, Meli; Imron, Khoiri Ahmad Fauzi; Anugraheni, Junaidah; Syafirah, Dina; Sari, Winda Puspa; Heris, Erfian (Universitas Nahdlatul Ulama Surabaya, 2021)
Background: One form of prevention of dengue haemorrhagic fever is through increasing public knowledge and understanding of the incidence of dengue haemorrhagic fever. Objective: This study was carried out with the aim of knowing the effect of health education on increasing behaviour for the prevention of dengue hemorrhagic fever in community. Methods: This study used a research design in the form of a pre experimental design with one group pre-post test design approach. This research was conducted on September 5, 2021 at RT 01 Kali Pecabean Village, Candi Sub-District, East Java Province, Indonesia. The population of this research is all families who live in RT 01 Kali Pecabean Village. The number of research samples was 26 families that were determined by using a sampling technique in the form of purposive sampling. Families who became respondents in this study were represented by one of the family members who participated in social gathering activities. The inclusion criteria used were families who participated in health education activities conducted at regular social gatherings. The instrument used is The Dengue Haemorrhagic Fever Prevention Questionnaire (DHFPQ). The result of reliability test was .550 and the validity was .84. Analysis of the data used is the Wilcoxon Signed Rank Test with p-value < .05. Result: The results showed that there was an effect of health education on increasing behaviour for the prevention of Dengue Haemorrhagic Fever in the community (p-value .0000). Conclusion: With the results of this study, it is hoped that health workers are expected to increase public understanding through the provision of health education as a preventive measure against the incidence of Dengue Haemorrhagic Fever. In addition, health workers are also expected to provide assistance to the community.